THE ROLE OF NGO’S IN RURAL DEVELOPMENT IN INDIA - Singh, Sarjeet; Goswami, Prabhakar lal (Universal Research Reports, 2018)
India is a land of villages and the Government of India has been Implementing various rural development programs for the raise of rural Communities. Non-government organizations with their advantage of non- rigid, locality specific, felt need based, Beneficiary oriented and committed nature of service have established multitude of roles which can effect rural development. A number of NGOs have been working in rural area community development, besides government interventions. Realizing that the government alone Was not able to meet the challenges of the massive enormous tasks in the process of rural development, the non-profit, voluntary and non-governmental organizations had to be Involved in different phases and activities at the global, regional and local levels. Thus, in later phases, both the GOs and NGOs have been actively involved in transforming the lives of the rural poor. No doubt, NGOs have been constantly working day-in and day-out to solve various problems concerning children, women, senior citizens, environment etc.